2016
DOI: 10.3389/fpsyg.2016.00051
|View full text |Cite
|
Sign up to set email alerts
|

Observational Learning: Tell Beginners What They Are about to Watch and They Will Learn Better

Abstract: Observation aids motor skill learning. When multiple models or different levels of performance are observed, does learning improve when the observer is informed of the performance quality prior to each observation trial or after each trial? We used a knock-down barrier task and asked participants to learn a new relative timing pattern that differed from that naturally emerging from the task constraints (Blandin et al., 1999). Following a physical execution pre-test, the participants observed two models demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 54 publications
2
27
0
3
Order By: Relevance
“…That is, observing the work of others gives individuals an opportunity to learn what to do, not just how to do things. Attentional processes determine what is selectively observed and what information is extracted in the profusion of modeling influences (Andrieux andProteau 2016, Hanna et al 2014). Simple exposure to models does not in itself ensure learning (Bandura 1971).…”
Section: Learning From Observing the Work Of Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, observing the work of others gives individuals an opportunity to learn what to do, not just how to do things. Attentional processes determine what is selectively observed and what information is extracted in the profusion of modeling influences (Andrieux andProteau 2016, Hanna et al 2014). Simple exposure to models does not in itself ensure learning (Bandura 1971).…”
Section: Learning From Observing the Work Of Othersmentioning
confidence: 99%
“…Learning theory suggests that individuals learn from both direct experience with an activity (Arrow 1962, Epple et al 1996, Foster and Rosenzweig 1995, Newell and Rosenbloom 1981, Rosen 1972 and indirect experience from observing others (Bandura 1977, Banerjee 1992, Bikhchandani et al 1992, Hanna et al 2014). 1 Although these learning models are diverse, a common assumption is that the key learning input is informative signals (Andrieux and Proteau 2016, Bandura 1977, Camerer 2011, Hanna et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of the AO effects on motor performance can be modulated by several factors such as the observed model type , advanced information about the demonstration quality (Andrieux and Proteau, 2016), viewpoint (Watanabe and Higuchi, 2016), and visual guidance (D'Innocenzo et al, 2016). With respect to the observed model type, participants who were required to observe a four-segment timing task performed by a novice, expert, or both novice and expert models outperformed a control group on both total movement time and intermediate time of each segment in the immediate retention and transfer tests ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the observed model type, participants who were required to observe a four-segment timing task performed by a novice, expert, or both novice and expert models outperformed a control group on both total movement time and intermediate time of each segment in the immediate retention and transfer tests ). Using a similar task, another study (Andrieux and Proteau, 2016) found that learning was optimized when knowledge about the quality and characteristics of the demonstration (total movement time and intermediate time) was presented before each demonstration as opposed to after each demonstration. Learning, reflected by shorter response latencies and fewer errors, was also shown to be optimized following observation from a first-person perspective in contrast to a third-person perspective in another timing task-index finger lifting from a resting position (Watanabe and Higuchi, 2016).…”
Section: Introductionmentioning
confidence: 99%